The multifaceted roles of B lymphocytes in metabolic dysfunction–associated steatotic liver disease - Li, Huige; Xia, Ning (Frontiers in Immunology, 2024)
Recent evidence suggests that adaptive immune cells are important contributors to metabolic dysfunction-associated steatotic liver disease (MASLD, formerly non-alcoholic fatty liver disease, NAFLD). In liver biopsies from MASLD patients, the accumulation of intrahepatic B cells is positively correlated with the MASLD activity score. Hepatic B-cell infiltration is observed in several experimental models of metabolically induced steatohepatitis (MASH, formerly nonalcoholic steatohepatitis, NASH). Intrahepatic B2 cells have been shown to contribute to MASLD/MASH by activating T cells, macrophages and hepatic stellate cells, and by producing pathogenic IgG antibodies. In mice fed a MASH diet, selective depletion of B2 cells reduces steatohepatitis and fibrosis. Intestinal B cells are metabolically activated in MASH and promote Tcell activation independently of TCR signaling. In addition, B cells have been shown to contribute to liver fibrosis by activating monocyte-derived macrophages through the secretion of IgA immunoglobulins. Furthermore, our recent study indicates that certain B cell subsets, very likely regulatory B cells, may play a protective role in MASLD. This review summarizes the molecular mechanisms of B cell functions and discusses future research directions on the different roles of B cells in MASLD and MASH.